Spaces of Enslavement 2021
DOI: 10.7591/cornell/9781501715624.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Slavery and Social Power in Dutch Reformed Churches

Abstract: This chapter turns to the region's Dutch Reformed churches. It reviews the ways in which social power manifested within the church space, focusing in particular on the conditions of free and enslaved Black New Yorkers in these churches. The chapter argues that congregations' practices of selective admission to these spaces, exclusion from these buildings and church yards, and segregation within these spaces reinforced the social and racial hierarchies that supported slavery in their communities. It emphasizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research on the ethnic and religious makeup of the population has shown that it was, in fact, diverse (Cohen, 1981), but the diversity alone would not have made it different because we could say the same about Holland. Unique to New Netherland vis-à-vis most towns in Holland was the black population (Mosterman, 2011;Dewulf, 2016) and Native Americans, which created new challenges and opportunities with respect to trade, defense, diplomacy, sexual relations, and kin networks (Venema, 2003;Merwick, 2006;Otto, 2006;Romney, 2014). 5 The period of disruption and decline in the first Dutch Atlantic overlapped with these commercial and cultural developments, and the disruptions lasted a long time, from about 1645 to 1678.…”
Section: The First Dutch Atlanticmentioning
confidence: 99%
“…Research on the ethnic and religious makeup of the population has shown that it was, in fact, diverse (Cohen, 1981), but the diversity alone would not have made it different because we could say the same about Holland. Unique to New Netherland vis-à-vis most towns in Holland was the black population (Mosterman, 2011;Dewulf, 2016) and Native Americans, which created new challenges and opportunities with respect to trade, defense, diplomacy, sexual relations, and kin networks (Venema, 2003;Merwick, 2006;Otto, 2006;Romney, 2014). 5 The period of disruption and decline in the first Dutch Atlantic overlapped with these commercial and cultural developments, and the disruptions lasted a long time, from about 1645 to 1678.…”
Section: The First Dutch Atlanticmentioning
confidence: 99%